An analysis of Mexico’s organized crime: Narco-police and the dead women of Juarez - Wael Hikal (Freedom from Fear, 2009)
The current situation in Mexico has put the international community on alert due to the increas in crime rates; besides common criminality, bizarre behaviours have developed and are concerning Mexican citizens, their government and foreigners. This situation is out of the country’s control: in the past, attacks, massive kidnappings and homicides, as well as drug trafficking, were seen as isolated cases, but nowadays they have become recurrent and interconnected issues.